Effect of Polymer Flooding on Oil Recovery Using Reservoir Simulation, Umm-Faroud Field, Sirt Basin, Libya - Eljareh , Salem; Mahdi , Hameeda; A. Gwazi , Asmaa (Scientific Journal of University of Benghazi, 2024)
This work uses Polymer flooding as an Enhanced Oil Recovery (EOR) technique to increase the injected water viscosity to reduce the mobility ratio and improve sweep efficiency. A reservoir model was constructed using the reservoir-simulating method with Computer Modeling Group software (CMGs IMEX) to predict the oil production and water cut from Umm Foroud field, Sirt Basin, Libya. The models are based on data collected from 17 wells from the Umm Foroud field. Off which, five wells were utilized to build the models, while the other 12 wells were used to validate them. Three scenarios were made; the first was used to predict oil recovery with water injection only, with no polymer, the second model to predict oil recovery with polymer flooding of 10% concentration, and the third with polymer flooding of 20% concentration. The viscosity of water increased by two different concentrations of polymers. Results showed that when water viscosity increased, a significant reduction in mobility ratio occurred and hence, the sweep efficiency was improved. Oil production was improved (increased) in the second and third scenarios where the polymer-flooding scenario (10% and 20% polymer solution concentration) was used. However, the water cut was reduced when compared to water injection.